2003
DOI: 10.3200/aeoh.58.4.245-251
|View full text |Cite
|
Sign up to set email alerts
|

Trace Metal Content and Estimated Daily Human Intake from Chicken Eggs in Ibadan, Nigeria

Abstract: A total of 151 chicken eggs and 4 local chicken feeds purchased directly from the poultry farms, at the local markets, and along the roadsides of Ibadan, Nigeria, were analyzed for lead, cadmium, copper, iron, nickel, zinc, and cobalt by carbon graphite atomic absorption spectrophotometry. The authors found strong, positive correlations between the levels of metals in the feeds and the corresponding levels of metals in the eggs. The overall average concentrations (mg/kg) of each metal in eggs were as follows: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 31 publications
3
16
2
Order By: Relevance
“…Dietary inclusion of Co at 1.0% level however, significantly increased Co in all tissues. Although the increase in tissue level of Co did not affect the growth of fish, there is probability that average daily intake (ADI) of Co in man, which depends to a great extent on the food habit (Yamagata et al 1963, Biego et al 1998, Fakayode and Olu-Owolabi 2003, may increase through consumption of such fish. But, no safe recommended dietary allowance (RDA) has yet been established for cobalt, although a RDA for man is available for vitamin B 12 (2.4 µg per day) of which Co is an integral part (Anonymous 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Dietary inclusion of Co at 1.0% level however, significantly increased Co in all tissues. Although the increase in tissue level of Co did not affect the growth of fish, there is probability that average daily intake (ADI) of Co in man, which depends to a great extent on the food habit (Yamagata et al 1963, Biego et al 1998, Fakayode and Olu-Owolabi 2003, may increase through consumption of such fish. But, no safe recommended dietary allowance (RDA) has yet been established for cobalt, although a RDA for man is available for vitamin B 12 (2.4 µg per day) of which Co is an integral part (Anonymous 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Kato et al [20] determined the concentration in egg content as 0.0877 mg/kg d.m. and other authors [21,22] in egg content from hens kept in free range system, reported the average cobalt content in the range 0.0061 -0.01 mg/kg d.m. It was found that the supplementation of cobalt salts or vitamin B 12 only slightly increased the level of Co in egg content [20] .…”
Section: Chemical Evaluation Of Eggsmentioning
confidence: 99%
“…According to other papers, the average content of zinc in egg matter, depending on the system of hens breeding was 9.77 -13.75 mg/kg fresh mass. [21,22,31] . By increasing the content of Zn in the feed (zinc enriched yeasts) it is possible to slightly increase its concentration in egg content [24] .…”
Section: Zincmentioning
confidence: 99%
“…Giving animals feeds from areas with elevated content of trace elements results in their bioaccumulation in edible tissues, eggs and milk [15][16][17][18]. López Alonso [19] noted that domestic animals are an important source of food for humans and so provide a direct measure of pollutant transfer to humans.…”
mentioning
confidence: 99%